Grain boundary dissolution porosity in quartzofeldspathic ultramylonites: Implications for permeability enhancement and weakening of mid-crustal shear zones - Billia, M.; Timms, Nicholas Eric; Toy, V.; Hart, R.; Prior, D. (Pergamon-Elsevier Science Ltd., 2013)
Quartzofeldspathic ultramylonites from the Alpine Fault Zone, one of the world's major, active plate boundary-scale fault zones have quartz crystallographic preferred orientations (CPO) and abundant low-angle (<10° misorientation) boundaries, typical microstructures for dislocation creep-dominated deformation. Geometrically necessary dislocation density estimates indicate mean dislocation densities of ~109 cm-2. A significant proportion (~30%) of grain boundaries (>10° misorientation) are decorated by faceted pores, commonly with uniformly-oriented pyramidal shapes. Only grain boundaries with >10° misorientation angles in polymineralic aggregates are decorated by pores. Mean grain boundary pore densities are ~5 × 108 cm-2. Grain boundary pores are dissolution pits generated during syn-deformational transient grain boundary permeability, nucleating on dislocation traces at dilatant grain boundary interfaces. They have not been removed by subsequent grain boundary closure or annealing. Pore decoration could have led to grain boundary pinning, triggering a switch in the dominant deformation mechanism to grain boundary sliding, which is supported by evidence of CPO destruction in matrix quartz. Pore-decorated grain boundaries have significantly reduced surface area available for adhesion and cohesion, which would reduce the tensile and shear strength of grain boundaries, and hence, the bulk rock. Grain boundary decoration also significantly decreased the mean distance between pores, potentially facilitating dynamic permeability. Consequently, these microstructures provide a new explanation for strain weakening and evidence of fluid flow along grain boundaries in mylonites at mid-crustal conditions.